Stem cell and its derivatives as drug delivery vehicles: an effective new strategy of drug delivery system. Issue 1 (1st January 2021) - Fu, Hongwei; Wu, Yinan; Yang, Xiaobin; Huang, Shiyi; Yu, Fenglin; Deng, Hong; Zhang, Shu; Xiang, Qi
Abstract : Researches on drug delivery system (DDS) have made incredible progress, but there are still problems such as insufficient targeting and undesirable treatment efficiency. To improve the above problems, a stem cell-based DDS was developed. Stem cell and its derivatives (cell membranes, extracellular vesicles/exosomes) have been used as important drug delivery vehicles in the treatment of a number of human key diseases, such as genetic diseases, cancer and so on. For stem cells highly express chemokine receptors such as CCR2 and CXCR4, which can specifically bind to chemokines or cytokines produced in tissue injury sites, so they exhibit centripetal and homing properties, which is the reason why they are employed as DDS vehicles. Stem cell-based DDS effectively enhance the targeting and efficiency of drugs with low immunogenicity. We review the extremely prominent superiority of stem cells and its derivatives as drug delivery vehicles. Especially summarize the different targeting strategies and the major application in anti-tumor, anti-inflammatory, tissue repair and regenerative medicine fields. The challenges of stem cell-based targeted DDS are still how to enhance their targeting, selectivity, effectiveness, reducing immunogenicity, and fully exerting its immunomodulatory effects. We think stem cell and its derivatives-based DDS will demonstrate their significant prospects in the future.